ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI RENDAHNYA KEPUASAN PELANGGAN PRODUK LISTRIK PRABAYAR DI SEMARANG - Wahyuningtiyas, Atika (Master of Management Diponegoro University, 2013)
National Electric Power Company according to its commitment has to upgrade its service quality to the society as the only company supplying electrical power where the custoner satisfaction is become a very important matter. By maintaining the customer satisfaction means to upgrade good image of the company and minimizing customer complains. This study examined the impact four independent variables, ie quality of tools, easy use of tools, acquiring access token and customer complaint response on customer satisfaction.This research was conducted with a questionnaire to 95 APP PLN customer obtained by using purposive sampling techniques. Then conducted an analysis of data obtained in the form of quantitative and qualitative analysis. Quantitative analysis involves the validity and reliability testing, test classic assumptions, multiple regression analysis, Goodness of Fit test through regression coefficient (R2), F test and t test. Qualitative analysis is an interpretation of the data obtained in this study and the results of data processing is carried out by giving a description and explanation.The data that have met the test of validity, reliability, and test the assumptions of classical . These results indicate that all the independent variables tested are positive and significant impact on customer satisfaction through the F test and t test, whereas the number Adjusted R Square of 0.858 indicates 85,8% of the variation in customer satisfaction which can be explained by the fourth independent variable, where the remaining 14.2% is explained by other factors outside of the study.